Association between Hyperglycemia and Prostate Volume in Patients with Benign Prostate Enlargement : A Hospital Case-Control Study - Eriawan Agung Nugroho; Rickky Kurniawan (Journal of Biomedicine and Translational Research, 2017)
Introduction: Prostate is a male organ which might enlarge mostly, either benign or malignant. Hyperglycemia is one of the factor that increase the risk of  benign prostate hyperplasia. There is lack of studies which assessed the relationship between benign prostate hyperplasia and isolated hyperglycemia. The aim of this study was to evaluate the association between hyperglycemia and prostate volume in patients with benign prostate enlargement in dr. Kariadi Hospital Semarang.  Method: We conducted a retrospective analysis of clinical data which obtained from 640 men between 2010 and 2012 who admitted to the hospital with diagnosis of benign prostate enlargement. By their medical records, these patients were evaluated of their plasma glucose level and prostate volume by trans rectal ultrasound. The  presence  of  hyperglycemia  was  determined  based  on  the  American  Diabetes Association (ADA) and the European Association for the Study of Diabetes (EASD). Patients have already been diagnosed with controlled diabetes mellitus by an internist. We allocated the subjects into two groups: patients with hyperglycemia and non-hyperglycemia. Logistic regression analysis was used to assess whether hyperglycemia was associated with the increased risk of benign prostate enlargement.Results: Significant difference of prostate volume found between groups. Prostate volume was  significantly greater in hyperglycemia group compared with non-hyperglycemia ones in all sub-groups based on age (in decades). Odds Ratio (OR) in patients with hyperglycemia was 2.25 (95% CI: 1.23-4.11). By non-parametric Spearman test it obtained  Group 1 (P1) p = 0.000 and r = 0.669, group 2 (P2) it obtained p = 0.000 and r = 0.672, group 3 (P3) it obtained p = 0.000 and r = 0.415 which implied strong positive associationConclusion: Hyperglycemia and prostate volume were significantly associated in patients with benign prostate enlargement. Hyperglycemia became a significant risk factor  for  prostate  enlargement  in  patients  with  benign  prostate  enlargement  in dr. Kariadi Hospital Semarang.